Simple ‘delays’ vs. ‘administrative inactivity’: Notes for the conceptual study of the maximum time limits of administrative procedures and their non-compliance - Saavedra Bazán, Ernesto José (Revista de Derecho, 2024)
The author addresses key ideas for a conceptual study of the ’legal term’ and the ’reasonable term’ in prior-evaluation administrative proceedings, to associate them with the concepts of mere ‘delays’ and ‘administrative inactivity’. A series of opportunities for legislative improvements to the national general administrative regulations as well as for a shift of paradigms regarding the administrative proceeding itself are identified.